2021
DOI: 10.1109/access.2021.3101565
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Classification of Crowdsourcing Participants’ Reviews Text Based on LDA Topic Model

Abstract: The review text received by crowdsourcing participants contains valuable knowledge, opinions, and preferences, which is an important basis for employers to make trading decisions, and crowdsourcing participants to improve service level and quality. However, there are two kinds of emotional polarity in the review text, the attention paid to sentiment classification of review text with fuzzy emotional boundaries is insufficient. This paper proposes a supervised text sentiment classification method with Latent Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
0
12
0
2
Order By: Relevance
“…Proposed by Blei et al [ 19 ], LDA is a typical “bag of words” model that treats each text as a vocabulary frequency vector and as a collection of multiple sets of vocabularies. In addition, each group of vocabularies represents a topic, and text topics are extracted without considering the order of and relevance between the vocabularies [ 37 , 38 ]. Normally, an LDA builds its topic generation model through the following steps: (1) a topic is selected from the various topics in a text; (2) a vocabulary is chosen from the list of vocabularies corresponding to the topic selected; and (3) the process is repeated until all of the vocabulary in the text has been selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed by Blei et al [ 19 ], LDA is a typical “bag of words” model that treats each text as a vocabulary frequency vector and as a collection of multiple sets of vocabularies. In addition, each group of vocabularies represents a topic, and text topics are extracted without considering the order of and relevance between the vocabularies [ 37 , 38 ]. Normally, an LDA builds its topic generation model through the following steps: (1) a topic is selected from the various topics in a text; (2) a vocabulary is chosen from the list of vocabularies corresponding to the topic selected; and (3) the process is repeated until all of the vocabulary in the text has been selected.…”
Section: Methodsmentioning
confidence: 99%
“…MARS is a multivariate, nonparametric regression technique and a tool that accumulates several basis functions to explain nonlinear states [ 57 ]. Once objective variables are set and a set that contains selectable predictor variables is given, MARS can automate the entire model construction process, including separating meaningful and less appropriate variables, determining the interactions between predictor variables, dealing with the missing value problem by using variable clustering techniques, and avoiding overfitting by using numerous self-tests [ 38 , 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…The OCR technique is used for preprocessing to extract the text contained in images [21]. In addition, the latent Dirichlet allocation technique, LDA is used to extract topic words from the text [22][23][24][25]. Each extracted topic word is converted into an embedding vector using a pretrained word-embedding model.…”
Section: Sub-model Based On Topic (Topic Sub-model)mentioning
confidence: 99%
“…The conclusion shows that the combination of text encoder TF-IDF and support vector machine classifier with linear kernel achieved the best performance results. Huang et al [11] constructed a text classifier based on a support vector machine (SVM), random forest (RF), XGBoost, and GBDT algorithm and analyzed the comment text of crowdsourcing platform participants. The results showed that the accuracy of the GBDT text emotion classifier was better than the method.…”
Section: Related Researchmentioning
confidence: 99%
“…A large number of consumer reviews are generated on the online ordering platform. Text reviews contain rich semantic content, such as consumers' experiences, feelings, and preferences, which are important data for feedback on the food safety of online ordering [10,11]. At present, review text mining has been widely used in the commercial field to improve the quality of products and services.…”
Section: Introductionmentioning
confidence: 99%